Determinant of recovery, recurrence and recurrence-free interval of condyloma acuminata: A five-year cross-sectional data from a provincial referral hospital in Indonesia - Prasetyadi Mawardi; Maulana, Muhammad I.; Ellistasari, Endra Y.; Primisawitri, Pratiwi P.; Purnamasari, Rina (Narra J, 2026)
Condyloma acuminata is a common sexually transmitted disease caused by human papillomavirus infection and is characterized by frequent recurrence despite available therapies. This study evaluated recovery, recurrence, and recurrence-free interval across therapeutic modalities among condyloma acuminata outpatients at Dr. Moewardi Regional General Hospital, Surakarta, Indonesia, from January 2020 to December 2024. Using a cross-sectional analysis of medical records, 132 eligible patients were included and analyzed with bivariate tests. Treatment modality was not significantly associated with recovery (p=0.157), although recovery was highest with trichloroacetic acid (71.2%), followed by excision (66.7%), combination therapy (trichloroacetic acid + cryotherapy) (64.7%), and cryotherapy alone (33.3%). In bivariate analysis, type of therapy (p=0.025) as well as type of condyloma (p<0.001), sexual orientation (p=0.019), and HIV status were associated with recurrence, with the highest recurrence observed after excision (42.4%) and the lowest after cryotherapy alone (11.1%). Mean recurrence-free interval varied across modalities (cryotherapy 8.00±0.00; trichloroacetic acid (TCA) 15.92±28.49; excision 18.93±13.64; combination therapy 27.50±36.67 weeks), with the longest interval observed in the combination group. However, statistical analysis revealed that only types of condyloma, sexual orientation, and HIV status were associated with the mean recurrence time. Overall, recovery and recurrence patterns differed descriptively across treatment modalities, with excision showing the highest recurrence and cryotherapy alone the lowest. Recurrence outcomes varied according to treatment modality; however, no significant association was observed between therapy type and recurrence-free interval.